Suitability of Soybean-Blood Meal Mixture as Replacement of Fish Meal in Nile Tilapia (Oreochromis niloticus) Rations - Biketi, A.; Rachuonyo, H. A.; Manyala, J. O.; Fitzsimmons, K.; Egna, H. (Africa Environmental Review Journal, 2020)
Fish require high quality protein in their rations which is sourced from fish meal. However, its scarcity and competition for use in livestock feeds has caused escalation of prices thus limiting its use. A study was carried out to evaluate protein quality of soybean-blood meal mixture as fish meal substitute in diets for Nile tilapia. Control diet, Fish meal based diet (R1) with 30% crude protein was formulated using fish meal, maize flour, wheat bran, sunflower oil and mineral-vitamin premix. Test diets (R2, R3, R4 and R5) were formulated replacing 25%, 50%, 75% and 100% of fish meal protein with soybean-blood meal mixture. Amino acids were determined using HPLC (AOAC, 2005) procedure. Fish meal had higher (p<0.05) levels of lysine (78.1 mg/g), arginine (58.7 mg/g) threonine (42.8 mg/g), Valine (54 mg/g) isoluecine (45.5 mg/g) phenylalanine and tyrosine (51.6 mg/g), methionine and cysteine (38.4 mg/g) and tryptophan (11.5 mg/g) than soybean-blood mixture. Soybeanblood meal was superior (p<0.05) to fish meal in amino acid histidine (40.5 mg/g) and leucine (79.4 mg/g). Replacement demonstrated reduction (p<0.05) in all Essential amino acids, except Histidine and Leucine which increased (p<0.05) in amounts with fish meal replacement. Replacement of fish meal with soybean blood meal mixture indicated reduction (p<0.05) in chemical scores except Histidine and Leucine which increased. Tryptophan was the limiting amino acid in all replacement diets. Essential amino acid indices (EAAI) showed slight reduction (p<0.05) with replacement R1 (117%), R2 (113%), R3 (109%), R4 (104%) and R5 (100%). Though fish meal-based diet (R1) had highest EAAI, all replacement diets had EAAI above 90% hence Soybean blood meal mixture was identified to be of high nutritive value. The study revealed that fish meal substitution with soybean-blood meal mixture gave good quality feed for Nile tilapia.